Epidemiology and phenotype of Crohn's disease in a reference hospital in Lima - Peru - Paredes Méndez, Juan Eloy (2020)
Crohn's disease (CD) is a chronic inflammatory pathology of the digestive tract with great impact on the quality of life of patients.Global epidemiology is changing in recent years and its prevalence is increasing in Latin America. Objective: To evaluate the epidemiological characteristics, phenotype, clinical course, diagnosis and treatment of CD. Materials and methods: Retrospective, descriptive, observational study of patients diagnosed with CD from January 2004 to December 2019 in the gastroenterology service of the Guillermo Almenara Irigoyen National Hospital, Lima-Peru. Results: 55 patients with an averageage of 56 ± 8.2 years were included. Male predominance (62%). The average diagnosis time was 18 ± 6.1 months. The most frequent symptoms were: abdominal pain 72.7% and weight loss 60%. Extraintestinal manifestations occurred in 20%. The ileal location (36.4%) was the most frequent, followed by colonic (32.7%). The inflammatory phenotype predominated in half of the patients, followed by stenosing in 25.5%. The most frequent activity clinical and endoscopic was moderate. For induction and maintenance treatment, systemic corticosteroids and biological therapy with anti-TNF were the most widely used, respectively. Approximately a third of patients required surgery during the evolution of the disease. Mortality was 5.4%. Conclusions: CD is an increasingly frequent disease in our country, with epidemiological and phenotypic characteristics that differ from othercontinents.